Real-space density functional theory and time dependent density functional theory using finite/infinite element methods - Soba, Alejandro (2012)
We present a numerical approach using the finite element method to discretize the equations that allow getting a first-principles description of multi-electronic systems within DFT and TD-DFT formalisms. A strictly local polynomial function basis set is used in order to represent the entire real-space domain. Infinite elements are introduced to model the infinite external boundaries in the case of Hartree's equation. The diagonal mass matrix is obtained using a close integration rule, reducing the generalized eigenvalue problem to a standard one. This framework of electronic structure calculation is embedded in a high performance computing environment with a very good parallel behavior.